A modern view of the law of torts - Colyer, J. S. (John Stuart) (Commonwealth and international library., 1966)
A Modern View of the Law of Torts provides the important aspects of the law of torts, which is an area of law that covers the majority of all civil lawsuits. This book begins with a description of the civil rights of an individual who is wronged by another person, followed by a particular attention to the remedies that are available to people who are wronged by any of the standard torts. Chapters of this book are devoted to specific torts, such as negligence, defamation, and trespass. Specifically, the law of negligence has been fully dealt with, as more and more of the problems of the law of.